Electronic culinary reservations based on Android with the Scrum methodology and Firebase database. Issue 5 (March 2021) - Setiawan, R; Supriatna, A D; Hudawiguna, S; Roji, F F
Abstract: Culinary preservation activities in the process of ordering food or drinks in restaurants are the initial process in restaurant or cafe activities, the problem that occurs is the buildup of orders on the order note, and sometimes customer order errors or changes to orders by customers. The purpose of this study is to make electronic android-based culinary reservations using firebase as a realtime integrated database between tables, kitchens, and cashiers. The research method used is Agile Scrum with the product backlog, sprint, daily scrum, and sprint review stages with modeling using Unified Modeling Language diagrams. This study took a sample in one restaurant in Garut Regency. This research resulted in a prototype of a reservation application that can be used on Android smartphones for customer tables, kitchens section, and cashiers. This culinary reservation application can help improve service to customers by increasing order times faster, reducing the occurrence of booking errors, and reducing paper usage.